Those we drown - Goldsmith, Amy (Delacorte Press, 2023)
When seventeen-year-old friends Liv and Will are accepted in a semester-at-sea program, they are excited to spend six weeks aboard the luxury cruise ship The Eos, but after Will disappears the first night, Liv grows suspicious that something sinister is lurking below deck.